Green supply chain collaboration and incentives: current trends and future directions - Gunasekaran, Angappa; Subramanian, Nachiappan; Rahman, Shams (Elsevier, 2015)
This editorial piece discusses the current trends and future research directions in green supply chain collaboration and incentives. The discussion begins with evolution of green supply chain collaborations and few contributions made so far. The editorial piece introduces the special issue papers which address the green collaboration challenges and offers a general green collaboration research framework suggesting pathways for future research. The article ends with the open research questions in green supply chain collaborations and incentives.